A multi-factorial assessment of elite paratriathletes` response to two weeks of intensified training - Stephenson, B. T.; Leicht, C. A.; Tolfrey, K.; Goosey-Tolfrey, V. L. (International Journal of Sports Physiology and Performance, 2018)
Purpose: In able-bodied athletes, several hormonal, immunological and psychological parameters are commonly assessed in response to intensified training due to their potential relationship to acute fatigue and training/non-training stress. This has yet to be studied in Paralympic athletes. Methods: Ten elite paratriathletes were studied for five weeks around a 14-day overseas training camp whereby training load was 137% of pre-camp levels. Athletes provided: six saliva samples (one pre-camp, four during camp, one post-camp) for cortisol, testosterone and secretory immunoglobulin A; weekly psychological questionnaires (POMS and RESTQ-S); daily resting heart rate and subjective wellness measures including sleep quality and quantity. Results: There was no significant change in salivary cortisol, testosterone, cortisol:testosterone ratio or secretory immunoglobulin A during intensified training (p=0.090). Likewise, there was no meaningful change in resting heart rate or subjective wellness measures (p=0.079). Subjective sleep quality and quantity increased during intensified training (p=0.003). There was no significant effect on any POMS subscale other than lower anger (p=0.049) whilst there was greater general recovery and lower sport and general stress from RESTQ-S (p=0.015). Conclusions: There was little to no change in parameters commonly associated with the fatigued state which may relate to the training camp setting minimising external life stresses and the careful management of training loads from coaches. This is the first evidence of such responses in Paralympic athletes.